DEMOCRATIZATION OF MANAGEMENT IN MUNICIPAL PUBLIC SCHOOLS IN THE AMAZON OF PARÁ - Ladinilson do Rosário Pantoja, Pedro; Sousa, Raimundo (Revista Gênero e Interdisciplinaridade, 2026)
It is a study on municipal public school management, which aims to analyze how the process of democratization of management is configured in the Municipal School of Elementary School Quilombo dos Palmares, located in the urban space of the Municipality of Altamira-PA. This is a research with methodological theoretical framework based on historical and dialectical materialism. It results from studies in specialized materials and field research, in which questionnaires were applied to the school principal, pedagogical coordinator, representative of parents in the school board, teacher representative in the school board. The research revealed that the democratization of management in public schools requires effective engagement of all subjects who constitute the school community, there is a need for training for part of the members of the school board, and it is essential to develop and implement the Political-Pedagogical Project (PPP), aiming at innovation and the resignification of the set of relationships that establish the recognition and construction of identities, the achievement of participation, autonomy and transparency.